Modular cell-internalizing aptamer nanostructure enables targeted delivery of large functional RNAs in cancer cell lines - David Porciani (Nature Portfolio, 2018)
Large RNAs and ribonucleoprotein complexes have shown potential as novel therapeutic agents, but their targeted delivery to cells is still challenging. Here the authors present a modular aptamer nanostructure for intracellular delivery of RNAs up to 250 nucleotides to cancer cells.